Hindsight Bias, Risk Perception, and Investment Performance - Biais, Bruno; Weber, Martin (Management Science, 2009)
Once they have observed information, hindsight-biased agents fail to remember how ignorant they were initially; “they knew it all along.” We formulate a theoretical model of this bias, providing a foundation for empirical measures and implying that hindsight-biased agents learning about volatility will underestimate it. In an experiment involving 66 students from Mannheim University, we find that hindsight bias reduces volatility estimates. In another experiment, involving 85 investment bankers in London and Frankfurt, we find that more biased agents have lower performance. These findings are robust to differences in location, information, overconfidence, and experience.